Prevalence And Antimicrobial Susceptibility Pattern Of Methicillin-Resistant Staphylococcus Aureus (MRSA) Isolated From Clinical Samples At A Tertiary Care Hospital In Bangladesh (East West Medical College Journal, 2026)
Background: Staphylococcus aureus, including methicillin-resistant Staphylococcus aureus (MRSA) strain, can become resistant to several classes of clinically available antibiotics and causes skin infections and severe infections in the lungs, heart, and bloodstream. Methicillin-resistant Staphylococcus aureus (MRSA) pathogens are considered a serious global health threat, leading to increased mortality and antimicrobial resistance. Rates of MRSA in Bangladesh remain high, necessitating continuous surveillance. This study determines the prevalence and antimicrobial susceptibility pattern of MRSA isolated from the clinical samples in East West Medical College and Hospital (EWMCH), Dhaka, Bangladesh.Methods: This retrospective study was conducted from January 2024 to December 2024 in EWMCH, Dhaka, Bangladesh. 4127 clinical samples from inpatients and outpatients were examined. Staphylococcus aureus isolates were identified by standard microbiological methods (Gram staining, catalase test, coagulase test). S. aureus strains were tested for Methicillin resistance by using cefoxitin disc diffusion method. The antibiotic susceptibility pattern of all MRSA strains was determined by Kirby-Bauer disc diffusion method recommended by Clinical and laboratory standards institute (CLSI).Results: Out of 4127 clinical samples analyzed, Staphylococcus aureus was recovered from 206 (4.99%) samples. Out of 206 positive strains, MRSA accounted for 106 cases (51.45%). Highest percentage of MRSA cases were from respiratory samples (83.33%), followed by pus /wound swab (56.52%), urine (52.47%) and blood (34.21%). MRSA isolates were more common in indoor patients (58.16%) than in outdoor patients (45.37%). Regarding antibiotic sensitivity, the most sensitive antibiotic for MRSA isolates was linezolid (76.41%) followed by doxycycline (74.52%) and tetracycline (51.88%). For Urine sample the most sensitive antibiotic was nitrofurantoin (86.79%) for MRSA.Conclusion:The data in this study represents the snapshot of the alarming prevalence of MRSA in Bangladesh.The drug susceptibility pattern is sufficient to warn the clinicians to choose empiric therapy in case of these infections as MRSA isolates are not only resistant to beta lactams but also to other groups of antibiotics. To combat the situation strengthening of infection control programme including practice of standard and isolation based precautions, surveillance of infections, rational use of antibiotics, periodic review of empiric therapy and monitoring of disinfection and sterilization of equipment are urgent needs.EWMCJ Vol. 14, No. 2, July 2026: 124-129